PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR IPA MATERI EKSRESI SISWA KELAS VIII SMP NEGERI 13 PEMATANGSIANTAR TAHUN PELAJARAN 2021/2022 - Rosenta Purba, Ika; Lihardo Hulu, Irwan; Selvia Sitohang, Dini (Jurnal Metabio, 2022)
This study aims to determine the effect of audiovisual media use on science learning outcomes in the subject of Excretion for eighth-grade students at SMP Negeri 13 Pematangsiantar. The population in this study were 60 eighth-grade students of SMP Negeri 13 Pematangsiantar in the 2021/2022 academic year. The research sample was selected using cluster random sampling: class VIII A (Experimental Class) using audiovisual media and class VIII B (Control Class) using conventional methods. The instrument used in this study was a multiple-choice test consisting of 20 questions. Furthermore, the data obtained were analyzed to find the mean, median, mode, standard deviation, normality test, reliability, validity, and t-test. The data obtained were then analyzed using a t-test using SPSS 21. The results of this study indicate a significant effect between the use of audio-visual media on learning outcomes, with a probability value of 0.000 <α = 0.05, with a t-count of 7.688 > t-table of 1.699. Therefore, H_a is accepted and H_0 is rejected, meaning that the use of audio-visual media has an effect on the science learning outcomes of eighth-grade students at SMP Negeri 13 Pematangsiantar in the 2021/2022 academic year.